En los márgenes de un tópico poético: El "Passerulus" alicaído de Filippo Buonaccorsi (Callimachus Experiens) - Díaz Gito, Manuel Antonio (2014)
The aim of this study is the analysis of the treatment of a well-known classical topic in the tradition of the Roman erotic poetry, the poem to a pet-bird, by a representative Italian humanist of the Quattrocento. In this paper we present the text, translation and commentary of the “De passere Silviae/Fanniae” by Filippo Buonaccorsi, alias Callimachus Experiens.
Keywords: Buonaccorsi, Filippo,‏ -- 1437-1496; Poesía erótica